Influence of veneer quality on beech LVL mechanical properties - Daoui, Abdelhakim; Descamps, Clément; Marchal, Rémy; Zerizer, Abdellatif (Maderas. Ciencia y Tecnología, 2025)
The quality of peeled veneers is generally quoted considering 3 main criteria: surface roughness, thickness variations and lathe checking. This last criterion impacts on mechanical properties of byproducts. It is well known that lathe checking occurrence can be reduced applying a good hygrothermal treatment of the round-wood before peeling coupled with optimised setting of pressure bar on the peeling lathe. It is also well known that thicker the veneer is and more difficult it is to reduce lathe checking and the other veneer defects. The tendency being to manufacture more eco-friendly engineering wood products using less glue, it is of interest to design such products with thicker layers and so less glue lines. But using ticker veneers should lead to a deterioration of final products mechanical properties. To quantify this effect, we have made 20-21mm thick LVL (Laminated Veneer Lumber) boards of beech (Fagus sylvatica) with various compositions (veneers 1, 3 or 5 mm thick). In order to obtained veneers enclosing different grades, several bolts of a same tree have been peeled following 4 different modalities changing wood conditioning temperature (20 / 70°C) and pressure bar settings (bar acting or not). The quality of all the veneers has been quantified before gluing. In total, 12 sets of boards have been produced for non destructive and destructive mechanical tests. The main results of these exploratory experiments are: - a quite low weakening of LVL mechanical properties when increasing veneer thickness. - the non destructive prediction of MOE by vibration seems not so good on LVL with thick veneers, especially in the case of edgewise loading, probably because of the presence of important lathe checks. - in some configuration, and especially when using thick veneers, it could be benefit to load LVL flatwise rather than edgewise. - for the measurement of shear strength on LVL, the 5-point bending test increases its efficiency when increasing veneer thickness. To properly order in a hierarchy the different veneer criteria impacting on LVL mechanical properties, new tests should be repeated on different LVL boards homogeneous for given criteria of veneer quality.